THE STORY “ALEXANDER THE KING” — A FOLK LEGEND ABOUT ALEXANDER - Xudayberdieva, Shahnoza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article is devoted to the study of the story of “Iskandar Podsho” (“King Alexander”). Starting with the story “About Dorob”, following the traditional prologue, the events of the stories which are devoted to the adventure of Iskander in this work are thematic in nature. Each series of stories is called a dastan. In addition to one unnamed story (dastan), ninety-seven dastans are presented in the work. In the Eastern classical literature, a lot of works are connected with the name of Iskander, which glorify his courage, intelligence and wisdom. The following study informs on the plot, images and the way of expressing the story “Iskandar podsho” (“King Alexander”).